DIGITAL DIDACTIC PROVISION OF TEACHING INFORMATION COMMUNICATION TECHNOLOGY IN LOGISTICS SYSTEMS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
In the article, the large-scale reforms carried out in our country today will entail the formation of a system of continuing education in many ways. The training of qualified, deeply educated specialists who think in a new way, are able to successfully farm in market conditions, especially qualified personnel who can make extensive use of information technology, continues to be a requirement of the period. Su bois studied the integration of information and communication technologies (ICT) into all areas of modern logistics, the digital didactic provision of people's knowledge, practical problem solving and training.